2019
DOI: 10.5038/1936-4660.12.2.3
|View full text |Cite
|
Sign up to set email alerts
|

Embedded Remediation Is Not Necessarily a Pathway for Equitable Access to Quantitative Literacy and College Algebra: Results from a Pilot Study

Abstract: Courses in developmental and introductory mathematics are changing. Because nearly all students need mathematics coursework to graduate from a postsecondary institution, yet institutions consistently struggle to ensure that students of all demographics succeed in credit-bearing mathematics courses, student success in such courses may be viewed as an issue of social justice. In particular, there is a need for institutions to provide pathways through college-level mathematics courses that meet the needs of stude… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Given the difference in context for QL courses, it is necessary to disaggregate this group of students to examine relevant student outcomes under remedial and corequisite structures. Matz and Tunstall (2019) published a pilot study which included two QL courses at Michigan State University. The pilot included embedded support in an additional weekly class meeting, termed "enhanced" courses.…”
Section: National Findings From Corequisite Mathematics Implementationmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the difference in context for QL courses, it is necessary to disaggregate this group of students to examine relevant student outcomes under remedial and corequisite structures. Matz and Tunstall (2019) published a pilot study which included two QL courses at Michigan State University. The pilot included embedded support in an additional weekly class meeting, termed "enhanced" courses.…”
Section: National Findings From Corequisite Mathematics Implementationmentioning
confidence: 99%
“…The researchers found that students who had successfully completed a remedial course prior to taking enhanced QL earned significantly lower course grades than those who would have been required to take remediation, but instead participated in the enhanced QL course without additional remediation. The researchers conjectured that embedded remediation did not necessarily result in equitable outcomes for students given that students with additional prior remediation did not do as well as those without it (Matz and Tunstall 2019).…”
Section: National Findings From Corequisite Mathematics Implementationmentioning
confidence: 99%
“…Laverty et al (2016) developed a protocol that characterizes the extent to which assessment tasks from college science courses can elicit evidence of student engagement with scientific practices, crosscutting concepts, and core disciplinary ideas (National Research Council 2012). A follow-up study evaluated change over time in the nature of assessments in introductory biology, chemistry, and physics courses with respect to these three dimensions (Matz et al 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In the recitation sessions, students collaborated in groups of three or four peers to solve problems and then turned in their worksheets for grading. A subset of students in the course was enrolled in enhanced sections, meaning they additionally attended a recitation session on Wednesdays between the lecture and the laboratory sessions; an analysis of the efficacy of these enhanced sections is reported in Matz and Tunstall (2018).…”
Section: Contextmentioning
confidence: 99%